A Numerical Comparison of Outflow Boundary Conditions for Spectral Element Simulations of Incompressible Flows (Communications in Computational Physics, 2007)
Outflow boundary conditions (OBCs) are investigated for calculation of incompressible flows by spectral element methods. Several OBCs, including essential-type, natural-type, periodic-type and advection-type, are compared by carrying out aseries of numerical experiments. Especially, a simplified form of the so-called Orlanski's OBCs is proposed in the context of spectral element methods, for which a newtreatment technique is used. The purpose of this paper is to find stable low-reflectiveOBCs, suitable and flexible for use of spectral element methods in simulation of incompressible flows in complex geometries. The computation is firstly carried out fora 2D simulation of Poiseuille-Bénard channel flow with Re=10, Ri=150 and Pr=2/3.This flow serves as a useful example to demonstrate the applicability of the proposedOBCs because it exhibits a feature of vortex shedding propagating through the outflow boundary. Then a 3D flow around an obstacle is computed to show the efficiencyin the case of more general geometries. Among the tested OBCs, the advection-typeOBCs are proven to have better behavior as compared with the others.
Keywords: Spectral element methods; outflow boundary conditions; incompressible flows.